YouTube as a source of information for retinopathy of prematurity in the Arabic language. (2nd January 2023) - Raffa, Lina; Alattas, Khadijah; Akeely, Omar; Awadh, Mohammed
Abstract: Retinopathy of prematurity (ROP) is a leading cause of blindness in infants thus it is important to raise awareness about this disease. As online platforms are a popular source of medical information; the purpose of this study is to evaluate the credibility of the content of YouTube videos on ROP in the Arabic language. The first 40 relevant videos were included and were independently reviewed by two ophthalmologists employing six assessment tools: reliability, accuracy, quality, comprehensiveness, overall viewer experience, and usefulness. Out of the 40 videos that were analysed, only 29 were considered useful. The mean DISCERN score of the videos was 32 indicating poor quality. Furthermore, 70% of the videos were completely accurate, but only 5% were fully comprehensive. Regarding the global quality score, only four videos were of excellent quality/flow (10%), while 15 were generally poor with the poor flow (37.5%). Viewer experience was assessed as fair to very poor in 22 videos (55%). The overall quality of the content in YouTube videos was poor, rendering this platform an unreliable source of information about ROP. However, given its high level of engagement, the medical community could hone its potential for raising awareness about ROP by creating entertaining useful content.